Harmonization of Islamic Inheritance Law and Indonesian Customary Law Regarding The Acceleration of Inheritance Distribution: Legal Philosophy Study - Azharuddin, Azharuddin (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Abstract The concept of rahmatan lil 'alamin is a main characteristic in Islamic law, so that every existing law must not burden humans. Nowadays, inheritance problems often arise from the application of its distribution, where the heir (child) wants the distribution to be expedited, this is in accordance with the principles of Islamic inheritance. The other party (wife) is reluctant to grant her child's wishes, this is in accordance with the culture and customs of Indonesian society. This research is purely normative law, where the data only focuses on library materials, the legal philosophy approach is the main analytical tool, and is assisted by a comparative law approach. The results of the study show that the problem of expediting inheritance sometimes ends with a child's lawsuit against his mother in court, so that it often causes social polemics where the child is usually declared an unfilial child or a child who prays for his parents to die. This article provides an analysis related to this problem, because of the conflict between the principles of Islamic inheritance and the culture of Indonesian society, the analysis pattern in this article uses Islamic legal philosophy, so that a fair inheritance distribution is obtained for the Indonesian Muslim community. This article requires that the distribution of inheritance be adjusted to Indonesian culture, at least after all customary and cultural matters regarding the management of the deceased have been completed . [Konsep rahmatan lil‘alamin merupakan khas utama dalam hukum Islam, sehingga setiap hukum yang ada pasti tidak membebani manusia. Dewasa ini sering terjadi permasalahan waris yang beranjak dari penerapan pembagiannya, di mana ahli waris (anak) menghendaki pembagian disegerakan, hal ini sesuai dengan asas waris Islam. Pihak lainnya (istri) enggan mengabulkan keinginan anaknya, hal ini sesuai dengan kultur dan adat kebiasaan masyarakat Indonesia. Penelitian ini murni hukum normatif, di mana datanya hanya berfokus kepada bahan kepustakaan saja, pendekatan filsafat hukum menjadi alat analisis utama, dan dibantu dengan pendekatan perbandingan hukum. Hasil penelitian menunjukkan bahwa permasalahan penyegeraan warisan kadangkala berujung gugatan anak kepada ibunya ke pengadilan, sehingga tidak jarang menimbulkan polemik sosial di mana si anak biasanya dinyatakan sebagai anak durhaka atau anak yang mendoakan orangtuanya meninggal. Tulisan ini memberikan analisis terkait permasalahan tersebut, karena terjadinya pertentangan antara asas kewarisan Islam dengan budaya masyarakat Indonesia, pola penganalisisan dalam artikel ini memakai filoshofi hukum Islam, sehingga didapatkan pembagian warisan yang berkeadilan bagi masyarakat Islam Indonesia. Artikel ini menghendaki supaya pembagian warisan disesuaikan dengan budaya Indonesia, minimal setelah selesai semua urusan adat dan budaya dari kepengurusan mayyit.]